Genetic resistance to gastrointestinal parasites in Dorper and Red Maasai X Dorper lambs in coastal Kenya - Baker, R.L.; Reynolds, L.; Mwamachi, D.M.; Audho, James O.; Magadi, M.; Miller, J.E. (Small Ruminant Collaborative Research Support Program, 1993)
This study quantifies comprehensively both within and between breed differences in resistance to natural infection with gastrointestinal parasites. This research programme was developed from an earlier study in coastal Kenya involving Dorper and Red Maasai X Dorper sheep. It is now part of an ILCA Pan-African study on genetic resistance to endoparasites in small ruminants. Results are Reported here for the lamb born born in 1991 and 1992. In both years the F1 ewes had a higher reproductive performance than Dorper ewes, due almost entirely to a higher lambing rate. The lambing rate includes both pregnancy rate and ewe disposal rate from mating to lambing. The number of ewes disposed of in 1991 were only 14 and 3 in 1992. Over the two years combined the F1 ewes had a higher pregnancy rate than Dorper ewes which was then reflected in the number of lambs weaned per ewe mated. The twinning rate was low with 5 sets of twins born in 1991 and 7 sets in 1992, with no difference between ewe breeds in twinning frequency.